2010
DOI: 10.1016/j.cveq.2010.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Laminitis and the Equine Metabolic Syndrome

Abstract: Although much has been written about laminitis in the context of its association with inflammatory processes, such as dietary carbohydrate overload and endotoxemia, [1][2][3][4][5] recognition is growing that most cases of laminitis examined by veterinarians in private practice are those associated with pasture grazing, obesity, and insulin resistance (IR). 6,7 The term endocrinopathic laminitis has been adopted to classify the instances of laminitis in which the origin seems to be more strongly associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 73 publications
1
43
0
Order By: Relevance
“…In contrast, the interstitial glucose concentration of obese horses in which IR has been demonstrated using CGIT tends to be more variable over time, runs relatively high within the reference range, and frequently exceeds the high end of the reference range. 55 We have also demonstrated that, when undertaken at the same time as a standard CGIT, there is very high correlation and concordance between results for both methods. clinical circumstances.…”
Section: 35657mentioning
confidence: 80%
See 3 more Smart Citations
“…In contrast, the interstitial glucose concentration of obese horses in which IR has been demonstrated using CGIT tends to be more variable over time, runs relatively high within the reference range, and frequently exceeds the high end of the reference range. 55 We have also demonstrated that, when undertaken at the same time as a standard CGIT, there is very high correlation and concordance between results for both methods. clinical circumstances.…”
Section: 35657mentioning
confidence: 80%
“…Dietary adjustments must strive to deliver a ration that is characterized by a low NSC content (low glycemic index) in order to both address obesity and minimize phases of hyperinsulinemia that are exacerbative to the laminitic condition. 55,61 As is the case in other species, dietary management represents a very important component of treatment of both IR and DM in horses. The optimal diet for management of DM in horses is unknown, but a low glycemic ration characterized by high fiber content, low NSCs, and added calories in the form of fat is regarded as a logical choice.…”
Section: 35657mentioning
confidence: 99%
See 2 more Smart Citations
“…For the determination of glucose level by means of glucometer (Glucosens 1040), blood samples were collected at 1, 5, 15, 25, 35, 45 , 60, 75 , 90, 105, 120, 135 and 150 minutes after administration of a bolus. In total, blood samples were collected for 2.5 h [13,26,27] . Sterile technique was maintained throughout the collection process.…”
Section: Experimental Horsesmentioning
confidence: 99%